Penerapan Inovasi Mesin Pencacah Limbah Organik Bertenaga Surya pada Lahan Jagung di Desa Langko, Janapria - Rahmi, Desiana; Bayu, Irfan (Lembaga Publikasi Ilmiah Nusantara, 2025)
The issue of agricultural organic waste management remains a challenge at the farmer level, especially in rural areas such as Langko Village, Janapria District. Corn plant waste, such as stalks and leaves, is often discarded without being utilized, even though it has the potential to be processed into compost or animal feed. This study aims to implement and evaluate the effectiveness of an innovative solar-powered portable organic waste shredder in supporting sustainable agricultural practices. The machine is designed using a 200-watt solar panel system with a shredding capacity of approximately 50 kg/hour. The implementation methods include socialization, technical training, and field trials on corn fields owned by local farmer groups. The results show that the use of the machine significantly accelerates the shredding process by up to 60% compared to manual methods. Additionally, the use of solar energy reduces dependence on fossil fuels and operational costs. Farmers responded very positively, with 87% expressing interest in continuing to use the device. This innovation is considered effective, environmentally friendly, and suitable for small to medium-scale farming. These findings recommend the adoption of similar technology in other agricultural regions with comparable characteristics. Future development can focus on increasing machine capacity and integrating it with automatic composting systems.